Nε-carboxyethyl-lysin influences atherosclerotic plaque stability through ZKSCAN3 acetylation-regulated macrophage autophagy via the RAGE/LKB1/AMPK1/SIRT1 pathway - Zhongwei Liu; Jing Liu; Xiqiang Wang; Yong Zhang; Yanpeng Ma; Gongchang Guan; Ya Yuwen; Ni He; Hanxiu Liu; Xingfeng Yu; Sen Ma; Junkui Wang; et al. (Cardiovascular Diabetology)
Abstract Atherosclerosis, a chronic inflammatory condition characterized by plaque formation, often leads to instability, particularly under Type 2 diabetes mellitus (T2DM) conditions, which exacerbate cardiovascular risks. However, the molecular mechanisms underlying this process remain incompletely understood. In this study, we investigated the correlation between acute coronary syndrome (ACS) and serum levels of Nε-carboxyethyl-lysin (CEL), a prominent advanced glycation end product (AGE) elevated in T2DM, in a cohort of 225 patients with coronary artery disease. Using a murine model of atherosclerosis complicated by T2DM, we examined the effects of CEL on plaque stability and macrophage autophagy. Our findings revealed that elevated serum CEL levels are independently associated with increased ACS incidence. Metabolomic profiling identified CEL as a key AGE contributing to plaque instability in diabetic conditions. Mechanistically, CEL disrupted macrophage autophagy and plaque stability by perturbing the Receptor for Advanced Glycation End products (RAGE)/Liver Kinase B1 (LKB1)/AMP-activated Protein Kinase 1 (AMPK1)/Sirtuin 1 (SIRT1) signaling cascade. This pathway further regulated autophagic activity through SIRT1-mediated acetylation of Zinc Finger with KRAB and SCAN Domains 3 (ZKSCAN3). These findings highlight CEL’s critical role in promoting plaque instability in T2DM by impairing key molecular pathways that regulate autophagy, offering potential therapeutic targets for managing atherosclerosis in diabetic patients.